Police Operation During Upsurge of Violence in Western Kingston - G. Morgan (Jamaica : G. Morgan, 1960)
This is an image of police searching pans beside a house during an upsurge of violence in Western Kingston.
Good Condition Copyright- JIS
This image is not digitized
This image is available on the Special Collections Floor.
Keywords: Law Enforcement. -- Photographs. -- Jamaica; Photograph